2018
DOI: 10.1021/acs.jced.7b00912
|View full text |Cite
|
Sign up to set email alerts
|

Study of Deep Eutectic Solvent on the Base Choline Chloride as Entrainer for the Separation Alcohol–Ester Systems

Abstract: Choline chloride-based deep eutectic solvent (DES) was tested for the separation of azeotropic mixtures of ethanol−ethyl acetate, n-propanol−n-propyl acetate and nbutanol−n-butyl acetate via liquid−liquid extraction. The mixture of choline chloride with malonic acid with a molar ratio of 1:1 was used. Extraction experiments were conducted with the ternary mixture ethanol−ethyl acetate−DES at temperatures 293.15, 303.15, and 313.15 K and with ternary mixtures npropanol−n-propyl acetate−DES and n-butanol−n-butyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Most of the works are devoted to the structure and dynamical properties of DESs to understand how those relate to the composition. Another important direction is low molecular weight compounds in DESs with a main focus on the development of separation techniques for CO 2 and SO 2 removal, as well as biofuel purification [ 9 , 25 , 26 ]. In nanotechnology, DESs are applied as solvents for the development of nanoparticles [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the works are devoted to the structure and dynamical properties of DESs to understand how those relate to the composition. Another important direction is low molecular weight compounds in DESs with a main focus on the development of separation techniques for CO 2 and SO 2 removal, as well as biofuel purification [ 9 , 25 , 26 ]. In nanotechnology, DESs are applied as solvents for the development of nanoparticles [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shang et al suggested that deep eutectic solvent ChCl/Urea (1:2) could be used for extractive distillation for the separation of ethanol-water [24]. The study of Samarov [25] tested Choline chloride-based deep eutectic solvent (DES) for the separation of azeotropic mixtures of ethanol-ethyl acetate, n-propanol-n-propyl acetate and n-butanol-n-butyl acetate via liquidliquid extraction. Some researchers believed that azeotropic phenomenon was broken because hydrogen bond sites which exist in DES have strong solvation with polar substances, thus changing the relative volatility [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The wide application of ILs is held back by their high cost, evidences for their toxicity and lack of biodegradability [23,24]. In this sense increased attention is drawn toward alternative liquids with similar physico-chemical properties, i.e., deep eutectic solvents (DES) [25][26][27], and especially their subclass: natural deep eutectic solvents (NADES) [28]. NADES are composed of two or more natural components, which interact via strong hydrogen bonding with formation of a liquid with the melting temperature much lower than those for individual components.…”
Section: Introductionmentioning
confidence: 99%